Mechanical and thermal evaluation of different types of PCM–concrete composite panels. Issue 2 (3rd April 2017) - Niall, Dervilla; Kinnane, Oliver; West, Roger P.; McCormack, Sarah
Abstract: The thermal mass of construction materials can be used to reduce the energy required for heating and cooling buildings. The heat storage capacity of concrete can be increased by incorporating phase change materials (PCMs) and hence providing a latent heat storage capacity. However, the addition of PCMs to concrete can reduce its conductivity due to the low conductivity of the PCMs. This hinders the efficient utilisation of the additional heat storage capacity provided by the PCM. Two types of PCM–concrete composite panels were manufactured. Firstly, a panel was formed by adding microencapsulated paraffin to fresh concrete during the mixing process. Secondly, butyl stearate was vacuum impregnated into lightweight aggregate which was then included in the concrete mix. In order to counteract the reduction in conductivity caused by the PCM, a second group of PCM–concrete composite panels were made using ground granulated blast-furnace slag (GGBS) as a partial cement replacement. The use of GGBS results in a denser cement paste which, for a given aggregate type, increases the conductivity of the concrete. This study aimed to establish which type of PCM–concrete composite material was most effective at improving the thermal mass behaviour of the panel and also to evaluate the effect that the PCM had on the relevant properties of concrete. The effect of GGBS on the thermal performance of the panels is reported.